Jaringan Saraf Tiruan Backpropagation Untuk Memprediksi Jumlah Ekspor Buah-Buahan Menurut Negara Tujuan - Nurhidayana Nurhidayana; Irfan Sudahri Damanik; Rafiqa Dewi (Journal of Information System Research (JOSH), 2021)
This research aims to predict the number of exports of fruits by country of destination in the coming year based on data in the previous year. The application of a prediction is very important in conducting research. The method used in conducting this prediction is the artificial neural network (JST) with its Backpropagation algorithm. The architecture used in this study is 4-2-1, 4-4-1, 4-6-1, 4-8-1, 4-4-2-1, and 4-3-6-1. Test results obtained prediction of export of fruits according to destination country with 91% accuracy rate with 4-4-1 architecture